Research ethics review as one way to protect human subject and not only - Ispambetova, Botagoz (KAZGUU University, Nazarbayev University, 2018)
Ethics has gained much popularity and recognition in the field of research with the development of behavioral, medical and biomedical sciences resulting from unsuccessful studies involving human subjects which led to detrimental and lethal consequences (Sieber & Tolich, 2014). These instances of unethical research have led to the proposal of various codes of ethics, each aiming to protect human subjects from physical, emotional, and psychological harm. The Nuremberg Code of Ethics (1949), Helsinki Declaration (1964), and Belmont Report (1979) were introduced (Meltzoff, 2005) Today, at the institutional level, Institutional Review Boards (IRBs) or Institutional Research Ethics Committees (IREC) function to review research involving human subjects for maintenance of ethical considerations (McAreavey & Muir, 2011). These boards review research for ethics referring to the above-mentioned codes along with federal regulations and laws of the country.
Keywords: ethics review; Research Ethics; Institutional Review Boards